The psycho-sociological perspective on civilization: insights from Malik Bennabi Theory - Shehab, Elmekdad; Smati, Abdelkouddous (Penerbit Universiti Kebangsaan Malaysia, 2021)
Throughout history, civilizations have served as the highest level of human progress, and just like countries, empires or societies, they have always been prone to rise and fall. As a result, attempts to understand their dynamics, formation, and decline have been significantly important for sociologists, politicians, anthropologists and historians, both recently and in the past. One of those was the Islamic scholar Abdurrahman Ibn Khaldun, who tried in his book "Muqaddimah" to explain the rise and fall of states, and despite the uniqueness and distinction of his proposition, Ibn Khaldun's contributions confined to the temporal-spatial context that Ibn Khaldun tried to explore, and his theory has not been developed to explain the civilizational dynamics, especially the Islamic civilization. This matter has been noticed by Malik Bennabi, who succeeded in making remarkably systematic contributions to the topic. Through relying on the psycho-sociological essence of Ibn Khaldun's theory. So that, this paper attempts to present some insights from psycho-sociological approach of Malik Bennabi in explaining the rise and fall of civilizations, compared to some Western theories that have addressed the relative topics.